TINGKAT PENGETAHUAN REMAJA TERHADAP PROGRAM PIK-R DI KAMPUNG KB KOTA PEKANBARU - Desmita Sari; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
PIK-R is a program from the government which is a means and a place to provide information about youth. This PIK-R is one of the programs implemented in the Kampung KB where the Kampung KB itself is an area unit at the village or kelurahan level with certain criteria in its formation where there is an integrated family planning population program and family development that aims to improve the quality of life of the community. Adolescents in this clan village have the opportunity to explore topics around youth such as adolescent health that discuss dangerous risks faced by adolescents ranging from sexuality, HIV nad AIDS nad then life skills to family planning for teenagers. Teenagers in this village are expected to be a pioneer in the creation of good and tough teens for future generations. The purpose of this study is to determine the level of knowledge of adolescents to this PIK-R program and find out what factors influence the level of knowledge of adolescents. The theory used in this research is the theory of knowledge level. This research is a quantitative research with descriptive type. The population and sample in this study were all adolescents who took part in the PIK-R activities in these two kb villages. The sampling technique used in this study is probability sampling. Data collection is done by field observations and questionnaires. The analysis is done by means of descriptive statistics by describing the data obtained. The results of this study concluded that as many as (100%) of respondents were at the know level, then as many as (81.1%) at the comprehension level, (79.8%) at the application level, (52.8%) at the analysis level, (40.2%) at the synthesis level and the highest level was evaluation at (35.8%). Keywords: The Level of Knowledge, PIK-R, Adolescents, Kampung KB